Media representations of social housing before and during COVID-19: the changing face of the socially excluded. Issue 1 (1st December 2022) - Kuskoff, Ella; Buchanan, Chris; Ablaza, Christine; Parsell, Cameron; Perales, Francisco
Abstract: Existing research demonstrates that the mainstream media produces and reproduces highly stigmatising representations of social housing. Such representations are largely underpinned by a moral underclass discourse, which blames individuals' social exclusion on their own moral deficiencies. However, since the COVID-19 pandemic, social, economic, and political contexts have changed significantly, and problems that were once perceived to be the result of individuals' deficits are increasingly viewed as being beyond their control. It is therefore timely to revisit representations of social housing in the mainstream media, to examine whether such representations have also changed in line with shifting social and economic contexts. To this end, this article examines mainstream media representations of social housing in the Australian state of Queensland before and during the COVID-19 pandemic. Our findings highlight important changes in the discourses invoked in the media articles, underpinned by a shift in who is perceived as being socially excluded and why.